2009
DOI: 10.2174/157488609787354413
|View full text |Cite
|
Sign up to set email alerts
|

Current Management of Vomiting After Tonsillectomy in Children

Abstract: Formal retraction notice of article entitled Current Management of Vomiting after Tonsillectomy in Children (Curr Drug Saf. 2009 Jan;4(1):62-73) by Dr Y. Fujii. This article is being retracted as a result of: Failure of Dr. Fijii's institution as well as of himself to rationalize the legitimacy of the study and/or its data as stipulated in request by the Editors-in-Chief of the journals extended on April 9, 2012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 89 publications
1
10
0
4
Order By: Relevance
“…There have been several studies regarding acupuncture applications to relieve PONV in paediatric tonsillectomy and/or adenoidectomy cases with expectations of increased postoperative patient comfort and decreased antiemetic drug use (27). Schlager et al (28) reported that the laser acupuncture technique was effective in paediatric ocular surgery cases (strabismus) as witnessed by a decrease in the PONV rate from 85% to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…There have been several studies regarding acupuncture applications to relieve PONV in paediatric tonsillectomy and/or adenoidectomy cases with expectations of increased postoperative patient comfort and decreased antiemetic drug use (27). Schlager et al (28) reported that the laser acupuncture technique was effective in paediatric ocular surgery cases (strabismus) as witnessed by a decrease in the PONV rate from 85% to 25%.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of ondansetron in the ED reported that 38% (n = 12,620) of prescriptions were for reasons other than gastroenteritis in the ED. 15 Other indications of ondansetron are post-operativem, [44][45][46] chemotherapy, radiotherapy, 47,48 sedation, 49 or during pregnancy. 50 Recently, ondansetron has been prescribed for brain-related diseases like obsessive-compulsive disorders 51 or drug/alcohol addictions, [52][53][54] suggesting that it may influence other symptoms than vomiting.…”
Section: Discussionmentioning
confidence: 99%
“…Tras la pubertad el sexo disminuye un 13% por cada década de edad. El género no parece ser un factor de riesgo para la aparición de VPO en los niños, ya que hasta la pubertad no existen diferencias significativas entre niños y niñas (3,11,78). Un factor de riesgo específico es la ansiedad o el miedo al separarlos de los padres.…”
Section: Factores De Riesgounclassified
“…La pauta de profilaxis más conveniente será la que consiga una mayor reducción de aparición de VPO y menores efectos secundarios y a iguales porcentajes de reducción la que tenga el menor coste directo (77,78,80). Al igual que en los adultos, se sabe que es más eficaz la profilaxis con dos fármacos que con uno, de tal forma que si existe un riesgo igual o superior al 30% (Eberhart ≥ 2) se debe realizar profilaxis con dos fármacos.…”
Section: Profilaxis (Tabla Vi)unclassified
See 1 more Smart Citation